Stress-strain state of a drill string in well sections with “dog-legs” - Rachkevych, R. V. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2014)
During the research a drill string was simulated by a flexible beam. The flexible beam has a 3D deformation under external loadings. The system of vector differential equations of equilibrium is used for analysis of the stress-strain state. The mathematical model takes into consideration a body weight and stiffness of a drill string, axial force, torsional moment and reactions of a hole wall. The deformation of a drill string elastic line with external diameter of 127 mm in a well “dog-leg” was analyzed in real operational conditions using the developed method. The author obtained the function of a drill string elastic line in 3D coordinate system. There were drawn the diagrams of normal stresses of bending around basic axes of inertia of a drill string cross-section. It is also noticed that the “dog-leg” increases these stresses twice.